World championship and olympic games experience influences future medal performance in track-and-field athletes - Fulton, T. J.; Baranauskas, M. N.; Chapman, R. F. (International Journal of Sports Physiology and Performance, 2022)
Some track-and-field national governing bodies send athletes to World Championship and Olympic Games (WC/OG) to gain experience that may positively impact future success, even though athletes may not be expected to place high or medal. However, it is unclear if this strategy is advantageous for future medal attainment.